The Influence of Nursing Care Documenting Behavior to the Completeness of Nursing Care Documentation at Hospital X - Muhammad Ardiansyah Saputra (Universitas Muhammadiyah Yogyakarta, 2018)
Nursing care documentation is a written evidence of nursing process given to the patient. It is very important to both the health care team, the patient and the hospital. The completeness of nursing care documentation at hospital X in February 2017 are 76.3% in assessment, 86.4% in diagnosis, 93.3% in planning, 96% in implementation and 92.2% in an evaluation. The purpose of this research is to discover the factors that influence the completeness of nursing care documentation at hospital X. This research is an analytical survey using cross-sectional study with 89 nurses as its samples. The data are analyzed using chi-square and multiple linear regression. The completeness of nursing care documentation is affected by knowledge (χ2 12.776), attitude (17.692) and supervision (14.417). The availability of nursing facilities has no influence on the completeness of nursing care documentation (3.384). Knowledge, attitude, availability of facilities and supervision has an influence on the completeness of nursing care documentation at 34.1%. The variable with the highest influence on the completeness of nursing care documentation is supervision (B 0.180). Knowledge, attitude, and supervision have an influence on the completeness of nursing care documentation. The availability of facilities has no influence on it and the one with the highest influence is supervision.